Créditos - Paula, Felipe Oliveira de (Em Tese, 2015)
EDITORES EM TESE: Felipe Oliveira de Paula; Gustavo Cerqueira Guimarães; João Alves Rocha Neto; Josué Borges de Araújo Godinho; Rafael Otavio Fares